Distinct vasculotropic versus osteotropic features of S. agalactiae versus S. aureus implant‐associated bone infection in mice. Issue 2 (29th December 2020) - Masters, Elysia A.; Hao, Stephanie P.; Kenney, H. Mark; Morita, Yugo; Galloway, Chad A.; de Mesy Bentley, Karen L.; Ricciardi, Benjamin F.; Boyce, Brendan F.; Schwarz, Edward M.; Oh, Irvin
Abstract: Osteomyelitis is a devastating complication of orthopaedic surgery and commonly caused by Staphylococcus aureus ( S. aureus ) and Group B Streptococcus (GBS, S. agalactiae ). Clinically, S. aureus osteomyelitis is associated with local inflammation, abscesses, aggressive osteolysis, and septic implant loosening. In contrast, S. agalactiae orthopaedic infections generally involve soft tissue, with acute life‐threatening vascular spread. While preclinical models that recapitulate the clinical features of S. aureus bone infection have proven useful for research, no animal models of S. agalactiae osteomyelitis exist. Here, we compared the pathology caused by these bacteria in an established murine model of implant‐associated osteomyelitis. In vitro scanning electron microscopy and CFU quantification confirmed similar implant inocula for both pathogens ( 10 5 CFU/pin). Assessment of mice at 14 days post‐infection demonstrated increased S. aureus virulence, as S. agalactiae infected mice had significantly greater body weight, and fewer CFU on the implant and in bone and adjacent soft tissue ( p < 0.05). X‐ray, µCT, and histologic analyses showed that S. agalactiae induced significantly less osteolysis and implant loosening, and fewer large TRAP + osteoclasts than S. aureus without inducing intraosseous abscess formation. Most notably, transmission electron microscopy revealed that although both bacteria are capable of digesting cortical bone, S. agalactiae have a predilection for colonizing blood vessels embedded within cortical bone while S. aureus primarily colonizes the osteocyte lacuno‐canalicular network. This study establishes the first quantitative animal model of S. agalactiae osteomyelitis, and demonstrates a vasculotropic mode of S. agalactiae infection, in contrast to the osteotropic behavior of S. aureus osteomyelitis.